Lake and channel-bottom temperatures in the Mackenzie delta, Northwest Territories - Ensom, T.P.; Burn, C. (Christopher R.); Kokelj, S.V. (Canadian Journal of Earth Sciences, 2012)
Temperature loggers were placed in 17 lakes and 13 channels throughout the Mackenzie Delta to determine the annual mean bottom temperature (̄Tb) and its spatial and temporal variation for June 2009 - June 2010. The lakes were classified as perched or connected, depending on the duration of their connection to the channel hydrologic system. Average ̄Tb values for nine perched lakes, five channels, and eight connected lakes distributed throughout the Mackenzie Delta were 5.5, 4.6, and 3.4°C, respectively. The range of ̄Tb among all instrumented water bodies in the Delta was 4.0°C. Over the year, bottom temperatures ranged from >20°C in midsummer to -5°C in midwinter, with relative stability between freezeup in mid-October and breakup at the beginning of June. Channel, perched, and connected lake ̄Tb, and mean annual nearsurface ground temperatures of -4°C in alluvial sedge wetlands and -2.25°C in forest, were used to estimate that about 60% of Delta lakes and nearly the entire channel network maintain through-taliks.